Madrasah Organizational Culture as the Foundation for Effective Educational Management - Zulkarnain (Sustainable, 2025)
Organizational culture plays a crucial role in shaping the effectiveness of educational management, particularly in madrasah as Islamic educational institutions that integrate academic and moral development. This study aims to examine organizational culture as a foundational element of effective educational management in the madrasah context. Employing a traditional literature review approach, this study analyzes relevant theories and empirical findings related to organizational culture, leadership, and educational management in madrasah and broader educational settings. The findings indicate that organizational culture, grounded in shared managerial values and Islamic moral principles, influences management processes, enhances teacher performance, and fosters a conducive learning environment. Furthermore, leadership—especially transformational and value-based leadership—emerges as a key factor in strengthening and sustaining organizational culture. Despite its strategic importance, the implementation of organizational culture in madrasah faces challenges such as resistance to change and inconsistencies between espoused values and actual practices. This study concludes that strengthening organizational culture through strategic management, character education, and collective stakeholder involvement is essential for achieving sustainable and effective educational management in madrasah.